Rates and risk factors for suicidal ideation, suicide attempts and suicide deaths in persons with HIV: a protocol for a systematic review and meta-analysis. Issue 2 (5th February 2021) - Wisnousky, Holly; Lazzara, Nick; Ciarletta, Matt; Pelton, Matt; Chinchilli, Vernon M; Ssentongo, Anna E; Ssentongo, Paddy
Abstract : Introduction: The prevalence of HIV/AIDS is high and is associated with psychiatric morbidity and suicide risk. The objective of this study will be to assess the rates of suicidal ideation, suicide attempts and suicide deaths in people living with HIV/AIDS (PLWHA). Methods and analysis: We present a study protocol for a systematic review and meta-analysis of studies reporting the suicidality outcomes (suicidal ideation, suicide attempts and suicide deaths) in PLWHA. PubMed (MEDLINE), Scopus, EMBASE, Cochrane Library, OVID (HEALTH STAR), OVID (MEDLINE), Joanna Briggs Institute EBP Database, Web of Science and PsychINFO databases will be searched from their inception until 1 January 2020. The primary outcome of interest will be the incidence of suicidality in PLWHA. In addition, we will delineate risk factors associated with suicidality in PLWHA. Citations, full-text articles and abstracts will be screened by four reviewers independently. Disagreements will be resolved through discussion. The study methodological quality (or bias) will be appraised using an appropriate tool. Random-effects meta-analysis will be conducted if we find that the studies are very heterogenous. For the suicidality outcome, probability of suicide risk will be reported. Relative risk ratios (with 95% CIs) will be reported for the effects of the risk factors. Potential publication bias will be assessed by conducting Egger's test and creating funnel plots. We will conduct additional analyses to explore the potential sources of heterogeneity (eg, age, sex and geographical location). Ethics and dissemination: No ethics clearance is required as no primary data will be collected. The results of this systematic review and meta-analysis will be presented at scientific conferences and published in a peer-reviewed journal. The results may inform clinical management of PLWHA and may guide future population-specific interventions. We will search PubMed (MEDLINE), Scopus, EMBASE, Cochrane Library, OVID (HEALTH STAR), OVID (MEDLINE), Joanna Briggs Institute EBP Database, Web of Science and PsychINFO from their inception until 1 January 2020. PROSPERO registration number: CRD42020161501.